Integrity Auditing and Data Sharing With Sensitive Information Hiding for Secure Cloud Storage - U, Divya; S, Nagaveni.; S, Pooja; R, Ramya.; N, Supritha. (International Journal of Computer Sciences and Engineering, 2025)
Along with the development of cloud computing more and more applications are moved to the cloud. With cloud storage services, users can remotely store their data to the cloud and realize the data sharing with others on the condition that the sensitive information is hidden in order to guarantee the integrity and confidentiality of the data stored in the cloud. Remote data integrity auditing is proposed to guarantee the integrity of the data stored in the cloud. In some common cloud storage systems such as the electronic health records system, the cloud file might contain some sensitive information. The sensitive information should not be exposed to others when the cloud file is shared. Encrypting the whole shared file can realize the sensitive information hiding but will make this shared file unable to be used by others. How to realize data sharing with sensitive information hiding in remote data integrity auditing scheme with time seal management still has not been explored In order to address this problem, we propose a remote data integrity auditing scheme with appropriate time management thereby providing limited access that realizes data sharing with sensitive information hiding in this paper. In this scheme, a sanitizer is used to sanitize the data blocks corresponding to the sensitive information of the file and transforms these data blocks’ signatures into valid ones for the sanitized file. These signatures are used to verify the integrity of the sanitized file in the phase of integrity auditing. As a result, our scheme makes the file stored in the cloud able to be shared and used by others on the condition that the sensitive information is hidden, while the remote data integrity auditing is still able to be execute efficiently. Meanwhile, the proposed scheme is based on Identity-based cryptography, which simplifies the complicated certificate management and also solves key exposure problem. The security analysis and the performance evaluation show that the proposed scheme is secure and efficient.